Instagram as an Islamic-Based Sexuality Education Platform (Case Study on Instagram Account @taulebih.id) - Intyaswati, Drina; Wulandari, Kharisma (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2023)
@taulebih is presented as a digital Islamic-based sex education platform to educate the public about the importance of sex education. @taulebih has various social media channels like LinkedIn, Facebook, TikTok, and Instagram. This research aims to find out how Instagram social media can be used to share educational information related to sexuality from an Islamic perspective by referring to Shannon and Weaver's Information Theory. This research was conducted using qualitative research methods and a case study approach, where data was collected through interview techniques. Research informants were selected using purposive sampling techniques. The research results show that the use of social media Instagram @taulebih through uploaded content containing Islamic-based sexuality education indicates positive changes in the knowledge and behavior of followers of Instagram.